Nymphaea lotus Linn. (Nymphaeaceae) Alleviates Sexual Disability in L-NAME Hypertensive Male Rats. (29th July 2019) - Kameni, Poumeni Mireille; Dzeufiet, Djomeni Paul Desire; Bilanda, Danielle Claude; Mballa, Marguerite Francine; Mengue, Ngadena Yolande Sandrine; Tchoupou, Tchinda Huguette; Ouafo, Agnes Carolle; Ngoungoure, Madeleine Chantal; Dimo, Theophile; Kamtchouing, Pierre
Abstract : Hypertension (HT) is a risk factor for erectile dysfunction (ED). This study aimed to evaluate the suppressive effect of Nymphaea lotus ( N. lotus ) on erectile dysfunction induced by NO deficiency in rat. 40 male rats equally divided into 4 groups received an oral treatment with 10 mg/kg/day of L-NAME, a NO blocker, during 4 weeks. Control group composed of 10 male rats received only distilled water (10 mL/kg). Thereafter oral treatments with N. lotus (75 and 200 mg/kg/day) and losartan (10 mg/kg/day) started and continued concomitantly with L-NAME in 3 groups for 4 additional weeks. Normal and negative controls received only distilled water. Sexual behaviour, orientation activities, anxiety, and penile histomorphology were evaluated at the end of treatment. L-NAME administration elevated significantly the blood pressure in male rats and decreased the copulatory rate by enhancing intromission latency and decreasing the numbers of intromission and ejaculation. However, the sexual motivation remains unaltered by chronic NO blockage suggesting that L-NAME induces penile dysfunction mainly by peripheral mechanisms. L-NAME chronic intake also induced anxiety, 4 weeks of N. lotus cotreatment prevented inhibitory effects of L-NAME on male sexual behaviour by shortening mainly ejaculation latency and postejaculatory interval while losartan does not. Losartan proved to be a more effective drug to decrease the blood pressure compared to the plant extract. Effectively, Nymphea lotus was able to reverse totally at 75 mg/kg the increment of hemodynamic parameters and the histological damage and exhibit anxiolytic-like effects in hypertensive male rats. Nymphaea lotus uses NO pathway to facilitate sexual responses at central and peripheral levels and can have a double medicinal use, against anxiety and erectile dysfunction.